Differences in the Level of Morphological Characteristics, Speed Abilities and Aerobic Endurance in Relation to the Team Position of Top Female Football Players - Izet Bajramovic; Slavenko Likic; Munir Talovic; Haris Alic; Eldin Jeleskovic; Goran Sporis (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
The aim of this paper is to determine the differences in the level of morphological characteristics, speed abilities and aerobic endurance according to the team positions of top female football players. The study included 18 female football players (age 21.33±3.67, body mass index 20.94±1.95). Female football players are classified under the following team positions: defenders (n = 7; 23±16.4 years), midfielders (n = 6, 20.5±14.3 years) and attackers (n = 5; 20±31.3 years). The following tests were used: 0-5m sprint (s), 0-10m sprint (s), 0-20m sprint (s), 0-30m sprint (s) and Beep test. Body mass index (BMI) was calculated based on the ratio of body weight (kg) and body height (cm). Based on the Beep test, the maximum oxygen consumption (VO2max) was calculated and presented in its relative value (ml/kg/min). The attackers had a higher body height (170.1±7.46) and weight (59.60±8.84) than those playing in midfield and defense positions. Also, the attackers were faster in the sprint on the 5m (1.17±.06), 10m (1.91±.06), 20m (3.27±.10) and 30m (4.51±.17) than female players in midfield and defense positions. Midfield players had higher level of VO2max (50.03±2.69) than female players in defensive and offensive team positions. Test results of univariate analysis of variance (ANOVA) showed that there are significant differences in the level of morphological features, speed and aerobic endurance capabilities between the top female football players, regardless of their team position (p>0.05). It is obvious that good speed abilities on short sprint sections as well as high level of aerobic endurance at high intensity are required regardless of players team position in the women's football. It is important to note that selection for team positions can not only be based on morphological characteristics, speed abilities and aerobic endurance of players. Also, tactical tasks as well as technical characteristics of players need to be considered for selection of team positions in the women's football.